The Female FTSE Board Report 2018: Busy going nowhere with the female executive pipeline - Vinnicombe, Susan; Doldor, Elena; Sealy, Ruth (Cranfield University, 2018)
This year we see two different pictures emerging in terms of women’s representation on FTSE 100 and FTSE 250 corporate boards. Since October 2017 the percentage of women on FTSE 100 boards has increased from 27.7% to 29%, meaning that if the current pace continues it is possible to reach the targeted 33% by the end of 2020. In total 264 women hold 305 directorships on FTSE 100 boards. The percentage of female Non-Executive Director (NED) positions is at the all-time high of 35.4%, whilst the percentage of female executive positions has flatlined at 9.7%. On a positive note, seven women hold a Chair position and 18 hold Senior Independent Directorships. A further 85 women hold 95 Chair roles on the various committees across FTSE 100 boards. In contrast, the percentage of women on FTSE 250 boards has only increased marginally from 22.8% in October 2017 to 23.7%, the percentage of female executive directorships has dropped from 7.7% to 6.4% and the number of all male boards has increased to ten. These present challenging conditions for meeting the 33% target in 2020.